Teachers ’evaluation of the extent to which basic education school principals practice ethical leadership in the Governorate of Al Dakhiliya, Sultanate of Oman - Al-Harasi, Raya Khalifa Fadel; Al-Hidabi, Dawood Abdulmalek Yahya (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying teachers ’evaluation of the extent to which principals of basic education schools in the Governorate of Al-Dakhiliya, the Sultanate of Oman, practice ethical leadership. To achieve the study’s objectives, the two researchers used the descriptive approach. A questionnaire was built and relied on a five-step scale, and the questionnaire was applied to a sample of (702) of Teachers of basic education schools in Al Dakhiliyah Governorate, Sultanate of Oman. The results of the study showed that the teachers ’evaluation of the extent to which principals of basic education schools in the Governorate of Al Dakhiliya, the Sultanate of Oman, practice ethical leadership, obtained an overall average (4.36 out of 5), i.e. a score of (very high) and at the level of the axes. Where the knowledge axis got the highest average (4.39 out of 5), followed by the goal axis with an average (4.38), then authority with an average (4.35) and finally confidence with an average (4.32), all of which have a degree of practice (very high), The results also showed that there are statistically significant differences at the level (α 5 0.05) according to the gender variables in all axes (goal, knowledge, authority, confidence) in favor of the "female" category with a difference in the arithmetic mean, as well as scientific qualification in all axes in favor of a bachelor’s degree. It is less, and there are no statistically significant differences due to the variable of job experience, the study concluded the importance of issuing a guide on administrative leadership ethics as a working guide for school administrations, as well as setting up specialized workshops and training programs to encourage principals, directorates’ departments and schools at various levels to practice moral leadership.